Microstructure and tempering behaviour of 28cr-2.5c-1w cast irons - Sasitorn Yeekew (2018)
© 2018 Trans Tech Publications, Switzerland. In this work, the effects of 1 wt.% tungsten addition and variation in tempering times on the microstructure and hardness of nominal 28 wt.%Cr high chromium irons were investigated. As-cast samples were destabilised at 1050o C for 4 hours and then hardened by air cooling. Tempering after destabilisation was carried out at 450o C for 2, 4 and 6 hours followed by air cooling. X-ray diffractometry, light microscopy and scanning electron microscopy were used to characterize the microstructures of the irons. The results show that the as-cast microstructure of the iron without W addition consisted of primary austenite dendrites with eutectic M7 C3 and eutectic austenite partially transformed to martensite. The iron with 1 wt.%W addition contained primary M7 C3 and eutectic M7 C3 in an austenite matrix. Destabilisation treatment of the austenite matrix in both irons allowed precipitation of secondary carbides and transformation to martensite during air cooling. Phase transformation of eutectic M7 C3 was also found in the iron with W addition. The formation of primary M7 C3 in the 1 wt.%W iron increased the as-cast macro-hardness from 500 (no W) to 576 HV30 . Destabilisation increased the macro-hardness up to 736 (no W) and 780 HV30 (1 wt.%W) since secondary carbide precipitation allowed austenite to transform to essentially martensitic matrices. At longer tempering times, the macro-hardness further increased up to about 820 HV30 .